1998
DOI: 10.1123/jsr.7.2.112
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Survey of Injury in Golfers

Abstract: In order to supplement the literature that describes individual injuries of the shoulder, carpal tunnel, and back in golfers, we administered a survey to demonstrate the incidence of golfers' injuries and describe the most frequent types. A questionnaire was administered to 1,790 members of the New York State Golf Association (amateur) under age 21. Three hundred sixty-eight players responded. Half of those responding had been struck by a golf ball at least on one occasion (47.6%), and 23% of the injuries were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 11 publications
0
31
0
3
Order By: Relevance
“…Collectively the incidence of LBP in the male golfer is 25-36% and 22-27% in the female golfer. [8][9][10][11][12][13][14][15][16] These ranges vary for a number of reasons. Many studies have low subject numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively the incidence of LBP in the male golfer is 25-36% and 22-27% in the female golfer. [8][9][10][11][12][13][14][15][16] These ranges vary for a number of reasons. Many studies have low subject numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The accepted survey response rate for a single mail-out to a large sample size is 15% to 30%. 5,[20][21][22][23][24] The survey instrument in this study was 1975 words in total, due to the large volume of information that was sought. While it is acknowledged that the size of the survey may result in a lower response rate, the investigators sought to collect comprehensive data to allow multiple factors to be analyzed in the statistical evaluation of factors possibly associated with golf-related injury.…”
Section: Discussionmentioning
confidence: 99%
“…examine the occurrence of injuries in golf-Several researchers [2,13] reported the lower back as ers. male player groups, [1][2][3][4][8][9][10][11][12][13] have been the focus of Theriault et al [9] and McNicholas et al [12] did not these studies. male player groups, [1][2][3][4][8][9][10][11][12][13] have been the focus of Theriault et al [9] and McNicholas et al [12] did not these studies.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…[1][2][3][4][8][9][10][11][12][13]18] Both amateur [1][2][3][8][9][10]12,13,18] and elite/ the most common injury site in males while Batt [3] professional golfers, [1,4,11] as well as male and fereported the wrist as the most common site injured. [1][2][3][4] tion of surveys by mail, [2][3][4][8][9][10][11] direct interview of Most of the golf-related injuries seen at hospital players, [1] and data collection at hospitals and sports emergency departments involved the head, [18] while medicine clinics. A summary of epidemiology studies is split the upper limb into regions and hence found it shown in table I.…”
Section: Epidemiological Studiesmentioning
confidence: 99%